Pengaruh Strategi Marketing dan Kepercayaan Pembeli Terhadap Keputusan Pembelian Produk Pakaian Melalui Akun Media Sosial Tiktok @Rucas.official - Febri Leo Sabilul Ashri; Fikri Shofin Mubarok (INDO PUBLISHING, 2025)
This study aims to analyze the influence of marketing strategies and buyer trust on purchasing decisions for clothing products through the TikTok account @rucas.official. This study uses the AIDA theory (Kotler and Keller) and marketing mix theory (Daryanto dan Hasiholan, 2019) with a quantitative approach and survey method. Data were collected through questionnaires to 100 respondents and processed using multiple linear regression analysis to explore the relationship between variables. The research findings show that marketing strategies have a significant influence on purchasing decisions, especially through innovative and interactive promotions carried out on TikTok. In addition, buyer trust also plays an important role in purchasing decisions, where factors such as information transparency, brand reputation, and product quality displayed in digital content greatly influence consumer purchasing interest. Thus, this study confirms that a combination of effective marketing strategies and increased buyer trust can encourage increased product purchasing decisions on digital platforms. Therefore, companies need to focus more on creating interesting and educational content, building interactions with audiences, and improving the quality of services and products to maintain customer loyalty in the digital era.